Elevating Language Learning with Chatbot Technology: Promise and Pitfalls - Nazirah Binti Mahmud (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2026)
Chatbots are emerging as popular tools for teaching and learning in foreign language education. Their features have transformed them into conversational companions, enabling learners to engage with the language more effectively. This review establishes a theoretical framework for chatbot technology in language learning by utilising two theories, namely constructivism and connectivism. To date, numerous chatbots have been developed and implemented, showcasing their potential to provide more interactive language experiences. However, studies have also acknowledged the limitations of these tools. This review aimed to offer an overview of the application of chatbot technology in language learning by discussing the underlying theoretical concepts, examining their usage and reviewing recent research to explore both the benefits and drawbacks of chatbots on learners’ language development. Future directions and innovations in this field were also presented.